Determination of Boron Content in Crackers Using Curcumin Reagent in a 2-Ethyl-1,3-Hexanediol Ligand through Spectrophotometric UV-Vis Absorption Spectra - Erni Yustissiani (LPPM Institut Studi Islam Sunan Doe, 2024)
Curcumin reagent is a reagent that produces rosocyanin complexes using the Uv-Vis spectrophotometry method. Optimum state of boron curcumin in EHD ligand (2-ethyl-1,3-hexanediol) at a wavelength of 551 nm. Linear calibration curve in the concentration range of 0.22-0.91 ppm in EHD with a correlation coefficient R2 of 0.9995 with a regression equation y = 0.9306x + 0.0005. This method produces a percent RSD of 0.303% with an average absorbance value of 0.226. The results of calculations with EHD ligands showed a detection limit value of 0.244 µg/L with a limit value of quantification obtained 0.815 µg/L. The measured boron levels in the five cracker samples analyzed by EHD were 1.35 mg/kg, 1.80 mg/kg, 1.99 mg/kg, 1.44 mg/kg, 2.05 mg/kg.